Crisis of governance and urban violence in Nigeria - Akinwale, Akeem Ayofe (African journal of criminology and justice studies, 2011)
This paper examines the crisis of governance and urban violence in Nigeria, using a documentary technique with an analysis of several theories including the Frustration and Aggression Theory, the Social Disorganization Theory, the Social Control Theory and Ecological Theory. It is argued that the outbreaks of violence have become unprecedented across the Nigerian cities, while successive attempts at promoting peace in the country are yet to succeed significantly. This situation is examined in the light of the dynamics of political instability and its concomitant outcomes. Several dimensions of urban violence including ethno-religious violence, electoral violence, youth militancy, and civil unrest are discussed. The findings in this paper suggest the need for fundamental changes in the extant attitude of government to violent groups in the Nigerian cities. Human rights and social justice should be given priority treatment in order to prevent resurgence of urban violence in Nigeria.